2020
DOI: 10.1007/s10103-020-03206-9
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation therapy as a high potential treatment modality for COVID-19

Abstract: COVID-19 is now a worldwide concern, causing an unprecedented pandemic. The infected cases show different symptoms based on the severity of the disease. In asymptomatic and non-severe symptomatic cases, the host immune system can successfully eliminate the virus and its effects. In severe cases, however, immune system impairment causes cytokine release syndrome which eventually leads to acute respiratory distress syndrome (ARDS). In recent years, photobiomodulation (PBM) has shown promising results in reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…Photobiomodulation (PBM) represents a new and emerging therapeutic modality for the treatment of coronavirus[ 1 ], [ 2 ] (including COVID‐19) and related inflammatory diseases such as pneumonia,[ 3 ], [ 4 ], [ 5 ] acute respiratory distress syndrome (ARDS),[ 6 ], [ 7 ], [ 8 ] chronic obstructive pulmonary disease (COPD)[ 9 ] and acute lung injury[ 10 ]. In PBM therapy, diseased or injured tissue is illuminated by a source of nonionizing electromagnetic radiation or EMR (delivered via lasers or LEDs) to stimulate physiologically beneficial photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Photobiomodulation (PBM) represents a new and emerging therapeutic modality for the treatment of coronavirus[ 1 ], [ 2 ] (including COVID‐19) and related inflammatory diseases such as pneumonia,[ 3 ], [ 4 ], [ 5 ] acute respiratory distress syndrome (ARDS),[ 6 ], [ 7 ], [ 8 ] chronic obstructive pulmonary disease (COPD)[ 9 ] and acute lung injury[ 10 ]. In PBM therapy, diseased or injured tissue is illuminated by a source of nonionizing electromagnetic radiation or EMR (delivered via lasers or LEDs) to stimulate physiologically beneficial photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, combined phototherapy approaches have been used to manage these COVID-19-related oral lesions [ 74 , 75 ]. The use of photobiomodulation has been claimed even in severe cases of acute respiratory distress syndrome in COVID-19 infected patients [76] . Clinical outcomes related to the application of photobiomodulation have shown successfully healing of oral lesions after few days [ 74 , 75 ].…”
Section: Biophotonics Approachesmentioning
confidence: 99%
“…These benefits appear to be related on the photobiomodulation's capacity to reduce or inhibit important substances involved in pain and inflammatory processes [74] , leading to an enhanced healing and improved quality of life for patients. A recent systematic review reported that photobiomodulation can significantly decrease the production of pro-inflammatory cytokines and some interleukins, reducing inflammation processes, regenerating damaged tissues [77] , and balancing the immune system [76] .…”
Section: Biophotonics Approachesmentioning
confidence: 99%
“…PBM stabilize the function of the immune system (drop the level of pro-inflammatory cytokines such as IL-1β, IL-6, IL-8, TNFα, and MCP-1 and improve the balance of IL-10) in severe COVID-19 cases, decreasing the impact of cytokine storm as the main cause of high mortality in ARDS patients [ 300 ].…”
Section: Photobiomodulation and Covid-19mentioning
confidence: 99%